Randomised trial reveals a mismatch between preferences for and hormonal responses to anthropogenic light colour temperatures - Solène Guenat; Jörg Haller; Nicole Bauer (PLoS ONE, 2025)
Public streetlights are universally used to improve visibility after dark and improve residents’ safety. However, anthropogenic light negatively impacts human health and well-being, biodiversity and energy consumption. Anthropogenic light impacts could be mitigated by technological changes optimising light characteristics, yet we know little of light colour temperature’s influence on well-being. Here, we aim to examine the impact of exposure to LED streetlights of 2700K, 4000K and 6500K on the impression of light, the feeling of safety, and the well-being (affect, self-reported stress and physiological stress). We used a parallel group field experiment with 77 participants, over 18 years old, in a small Swiss town with controlled light settings. Participants were randomly allocated to a light treatment through computer-generated randomisation. With 25–26 participants per treatment, we showed that participants had better impressions of warmer temperatures than of cold ones. Light temperatures did not influence affect, the feeling of safety or self-reported stress, yet the decrease in cortisol was stronger under 6500K than under 2700K. The observed lower hormonal stress levels in 6500K lights can be attributed to their resemblance to daytime light temperatures, while preferences for warmer lights reflect the expectations for night-time situations.